Association Between Residential Neighborhood Social Conditions and Health Care Utilization and Costs. Issue 7 (July 2020) - Zhang, Yongkang; Ancker, Jessica S.; Hall, Jaclyn; Khullar, Dhruv; Wu, Yiyuan; Kaushal, Rainu
Abstract : Background: Social factors are important drivers of health. However, it is unclear to what extent neighborhood social conditions are associated with total and preventable health care utilization and costs. Objectives: To examine the association of neighborhood social conditions with total annual and potentially preventable Medicare costs. Research Design and Subjects: Retrospective cohort study. Medicare claims data from 2013 to 2014 linked with neighborhood social conditions at the US census block group level of 2013 for 93, 429 Medicare fee-for-service and dually eligible patients. Measures: Neighborhood social conditions were measured by Area Deprivation Index at the census block group level, categorized into quintiles. Outcomes included total annual and potentially preventable utilization and costs. Results: After adjustment for demographics and comorbidities, patients with the least disadvantaged social conditions had higher total annual Medicare costs [$427; 95% confidence interval (CI), $200–$655] and similar potentially preventable costs (−$23; 95% CI, −$56 to $10) as compared with patients with the intermediate level social conditions. Patients with the most disadvantaged social conditions had similar total Medicare costs (−$22; 95% CI, −$342 to $298) but higher potentially preventable costs ($53; 95% CI, $1–$104) than patients with the intermediate level social conditions. Conclusions: Disadvantaged neighborhood conditions are associated with lower total annual Medicare costs but higher potentially preventable costs after controlling for demographic, medical, and other patient characteristics. Socioeconomic barriers may limit access and use of primary care and disease management services, resulting in a higher proportion of their health care costs going to potentially preventable care. Abstract : Supplemental Digital Content is available in the text.